Pengaruh Perceived Value dan Trust terhadap Loyalitas Nasabah Asuransi Syariah Prudential - Imsar Imsar; Juliana Nasution; Laila Hafni (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
According to Islamic law, Islamic insurance is an effort to protect each other and help between many people and parties through investment or assets, or among many people and parties through investment in the form of assets or tabarru'. Risk through contract (contract). This study aims to determine the effect of perceived value and trust on the loyalty of Prudential Islamic insurance customers, both in part and in general. The method used in this research is the quantitative method. The survey data was obtained from the survey by searching for the sample using the Slovin method. Survey was conducted on 83 customers of PT Prudential Life Assurance Syariah Division Tebing Tinggi. Questionnaire using hypothesis testing using SPSS software version 25 and using linear data using multiple linear regression analysis. The result of this research is that the variables of perception, perceived value and trust, have a positive and significant effect on loyalty. Second, the variable iperceived value also has a positive and significant effect on loyalty, and the itrust variable also has a positive and significant impact on the loyalty of Prudential Islamic insurance customers. Kata kunci : Perceived Value, Trust, Loyalty, Sharia Insurance